ANTIBACTERIAL ACTIVITY TESTING OF COLLASE LEAF EXTRACT (Centella asiatica L.) AGAINST Propionibacterium acnesBACTERIA - Bentar Jatmiko; Gigih Kenanga Sari; Mingle A Pistanty (Joseph: Journal of Science and Pharmacy, 2023)
Background: Propionibacterium acnes or P.acnes is a normal skin flora bacteria, but can be the cause of opportunistic infections in the form of acne. Generally, acne is treated using antibacterials aimed at reducing the colonization of bacteria. The centtella asiatica plant (Centtella asiatica) is a plant of one genus as Centella. Research shows that leaf ethanol extract (Centtella asiatica) has antibacterial activity. Purpose: This study aims to determine the antibattery activity of Centella asiatica leaf extract against Propionibacterium acnes and adequate concentration in inhibiting the growth of Propionibacterium acnes. Method: Centella asiatica leaves (Centella asiatica) were extracted by maceration method using 70% ethanol solvent. The dieprolwh extract was carried out phytochemical tests and antibacterial activity tests with the well method against Propionibacterium acnes. Clindamycin positive control 20μg, DMSO negative control 10%. Results: Phytochemical test of ethanol extract of centella asiatica leaves containing